Pengabdian Tes Parameter Atlet Taekwondo Oku Timur Menuju PORPROV Sumsel Tahun 2022 - Noviria Sukmawati; I Bagus Endrawan; Martinus Martinus (Community : Jurnal Pengabdian Pada Masyarakat, 2022)
Sport is a place for humans to explore their movement experiences and can improve the quality of individual health. The athlete development program has the potential to become a particular concern for every sports organization to attract potential athletes who can participate in the PORPROV SUMSEL 2022, mainly taekwondo. The biomotoric components developed by taekwondo include coordination, skill, speed, flexibility, muscle strength, balance, posture, power, and endurance. These can be used as test parameters to strengthen the athlete's morale and mentality. This community service activity aims to test, measure, and evaluate test parameters, including the TKJI test, endurance test, strength test, speed test, branching test and evaluation of athlete tests, especially in Taekwondo preparation for the 2022 PORPROV activities. The service's benefits are finding out and preparing, and evaluating athletes who have the potential to produce achievements in PORPROV activities in 2022 to match the expected achievement targets. The service results are shown in the test evaluation output based on the test parameters, including the TKJI, endurance, strength, speed, branching, and test evaluation. It shows that the physical tests follow the age and branching categories based on body weight and can determine the athlete's physique following the standard of achievement.